Co-Infection of Tuberculosis and COVID-19 in Children: A Case Report - Madeleine Ramdhani Jasin; Talitha Rahma Ayuningtyas; Achmad Rafli; Irawan Mangunatmadja; Wahyuni Indawati; Nastiti Kaswandani (Jurnal Respirologi Indonesia, 2024)
Background: Coinfection of TB and COVID-19 might occur, yet few evidence has been reported. Current COVID-19 pandemic also results in disruption at TB management in the community.Case: A 5-month-old boy came with recurrent seizure, with history of persistent cough and fever for 1 month prior, also positive possible TB contact. He was diagnosed with disseminated TB, involving miliary appearance in chest Xray also meningitis, coinfected with COVID-19.Discussion: During COVID-19 pandemic, TB service in the community is disrupted, resulting in delay in TB diagnosis, as observed in this patient, leading to severe manifestation. Coinfection of TB and COVID-19 can occur and may lead to more severe symptoms in either both diseases. Management of TB COVID-19 coinfected children is similar to those without COVID-19. Our patient received treatment consisting of 2 RHZE then 10 RH. Monitoring of symptoms and possible sequelae is necessary.Conclusion: Coinfection TB and COVID-19 may occur in children, and both can lead to more severe manifestation of each condition, particularly if diagnosis is delayed. Strengthening TB care in the community is essential so that there will be no delay in diagnosis, also no disruption in treatment and monitoring.